IMPLEMENTASI METODE BAMBOO DANCING UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL PADA SISWA KELAS V SEKOLAH DASAR - Candra Dewi (Universitas Muhammadiyah Ponorogo, 2016)
The purpose of this study dilator backs for their problems in learning social studies in primary school. In lessons students still tend to be passive and low learning outcomes. One of the factors behind these problems is in the learning process teachers have to use innovative learning so that students feel bored in learning. In connection with the above problems the classroom action research conducted by applying the method of bamboo dancing on learning IPS. This study includes several cycles and each cycle has phases including planning, execution and observation, reflection, revision planning. Data were obtained by using the method of observation, tests and interviews using tiangulasi techniques to obtain data validity. The subject of this research is a fifth grade elementary school students. The analysis technique used in this research is interactive analysis. Interactive analysis model has three components, namely: 1) Reduction of Data (Data Reduction), 2) Presentation of Data (Data Display), 3) Conslucion Drawing (verification). The results of this study there was an increase in the results of social studies of elementary school students through the application of methods of bamboo dancing in the learning process